Nigerian Higher Education Institutions Performance: Does Strategic Improvisation and Entrepreneurial Self-efficacy Matter? - Najafi Auwalu Ibrahim (Center for Communication Technology And Human Development (UniMAP), 2018)
Link to publisher's homepage at http://johdec.unimap.edu.my